Biological effects of Physalis peruviana L. (Solanaceae) crude extracts and its major withanolides on Ceratitis capitata Wiedemann (Diptera: Tephritidae) - Cirigliano, A. (2008)
Biological effects of Physalis peruviana crude extracts and its major withanolides (withanolide E and 4-ß-hydroxywithanolide E) were investigated on larvae and adults of the fruit fly Ceratitis capitata. High concentrations of crude extracts (10000 and 35000 ppm) in larval diet caused 100% mortality while low concentration (1000 ppm) caused significative differences in larval mortality, development delay and puparia length. Withanolide E and 4-ß-hydroxywithanolide E (500 ppm) also produced significative mortality on larvae. The application of crude extracts to adults drinking vessels caused significative lethal effects at 10000 and 35000 ppm. These data indicate that P. peruviana crude extracts and its two major withanolides could be used to develop baits to control C.capitata.